Relationship between Nutritional Knowledge, Healthy Eating Index, and Nutritional Status among University Students - Amaliah Amriani Amran Saru; Erona Wafaretta; Mitha Rahmilah; A. Citra Pratiwi; Muh. Syaiful Akbar (Journal of Scientific Insights, 2026)
Nutritional status among university students is influenced by various factors, including nutrition knowledge and dietary quality. This study aimed to analyze the relationship between nutrition knowledge, Healthy Eating Index (HEI), and nutritional status based on BMI categories among university students. A cross-sectional study was conducted among 88 university students. Nutrition knowledge was assessed using a structured questionnaire, dietary quality was evaluated using the Healthy Eating Index (HEI), and nutritional status was determined based on BMI categories. Data were analyzed using Chi-square tests to examine the associations between variables. The results showed that no significant association was found between nutrition knowledge and BMI status (p = 0.893). In contrast, HEI was significantly associated with BMI categories (p < 0.001). The distribution pattern showed that underweight respondents were predominantly classified as having poor HEI (82.5%), respondents with normal BMI had a relatively balanced distribution with many showing good HEI (53.5%), and overweight respondents also showed a high proportion of good HEI (80%). These findings suggest that although HEI is associated with BMI categories, higher HEI does not exclusively correspond to normal BMI In conclusion, nutrition knowledge was not associated with BMI status, while HEI was significantly associated with BMI categories, indicating that nutritional status is influenced by multiple factors beyond nutrition knowledge and diet quality alone.